Global handbook of inequality - Jodhka, Surinder S.; Rehbein, Boike (Springer, 2024)
Economic Process and World Regions -- Exploitation and Inequality -- Karl Marx and Inequalities of Social Class -- Angela Davis on a New Kind of Universality -- Social Inequality in Africa -- Wealth and Inequality.
Keywords: Ungleichheit